Electrophysiological Characteristics of Fetal Atrioventricular Block - Zhao, Hui; Cuneo, Bettina F.; Strasburger, Janette F.; Huhta, James C.; Gotteiner, Nina L.; Wakai, Ronald T. (Journal of the American College of Cardiology, 2008)
Electrophysiological Characteristics of Fetal Atrioventricular Block Hui Zhao, Bettina F. Cuneo, Janette F. Strasburger, James C. Huhta, Nina L. Gotteiner, Ronald T. Wakai Using serial magnetocardiography to define the electrophysiological characteristics of congenital atrioventricular block (AVB) in 28 fetuses, we found that fetuses with second-degree AVB or isolated third-degree (3°) AVB commonly exhibited complex, changing heart rate and rhythm patterns and had good outcomes. Of fetuses with structural cardiac disease, those with 3° AVB exhibited largely monotonous heart rate and rhythm patterns and poorer prognosis. Junctional ectopic tachycardia and/or ventricular tachycardia, which were not generally identified before referral, were seen in 30% of 3° AVB subjects, usually before 30 weeks’ gestation, and may be characteristic of an acute stage of 3° AVB. The purpose of our work was to define the complex electrophysiological characteristics seen in second- (2°) and third-degree (3°) atrioventricular block (AVB) and to longitudinally follow the development of atrial and ventricular heart rate and rhythm patterns with a goal of identifying heart rate and rhythm patterns associated with urgent delivery or neonatal pacing. The electrophysiological characteristics of congenital AVB before birth have not been extensively studied, yet the mortality from this disease is substantial. Along with advances in fetal therapies and interventions, a comprehensive natural history specific to the etiology of AVB, as well as the electrophysiological factors influencing outcome, are needed to best select treatment options. Twenty-eight fetuses with AVB were evaluated by fetal magnetocardiography; 21 fetuses were evaluated serially. Fetuses with 2° AVB and isolated 3° AVB showed: 1) diverse atrial rhythms and mechanisms of atrioventricular conduction during 2° AVB; 2) junctional ectopic tachycardia and ventricular tachycardia during 3° AVB; 3) reactive ventricular and atrial fetal heart rate (FHR) tracings at ventricular rates >56 beats/min; and 4) flat ventricular FHR tracings at ventricular rates <56 beats/min despite reactive atrial FHR tracings. In contrast, fetuses with 3° AVB associated with structural cardiac disease exhibited predominantly nonreactive heart rate tracings and simpler rhythms. Second-degree AVB, isolated 3° AVB, and 3° AVB associated with structural cardiac disease manifest distinctly different electrophysiological characteristics and outcome. Fetuses with 2° AVB or isolated 3° AVB commonly exhibited complex, changing heart rate and rhythm patterns; all 19 delivered fetuses are alive and healthy. Fetuses with structural cardiac disease and 3° AVB exhibited largely monotonous heart rate and rhythm patterns and poor prognosis. Junctional ectopic tachycardia and/or ventricular tachycardia may be characteristic of an acute stage of heart block.